Pengaruh Daya Saing, Harga, dan Kualitas Pelayanan terhadap Keberlangsungan Usaha - Khairil Anwardin; Akhmad Saufi; Handry Sudiartha Athar (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2021)
This aims to determine the effect of competitiveness, price and service quality on business continuity at the UD Kembang Ternak fish feed shop. In this study using an Associative with a quantitative approach. The sampling technique used purposive sampling, in order to obtain the number of respondents as many as 100 people. The data analysis technique used is multiple linear regression. The results of this study indicate that the competitiveness variable has a positive effect but does not have a significant effect on business continuity at UD Kembang Ternak. With a t value of 1.717 <1.98 and a significant value of 0.089> 0.05. Price variables have a positive effect but there is no significant effect on the sustainability of the business at the UD Kembang Ternak fish feed shop. With a t value of 0.020<1.98 and a significant value of 0.984> 0.05. Service quality variables have a positive and significant effect on the sustainability of the business at UD Kembang Ternak fish feed shop. With a t value of 15.711> 1.98 and a significant value of the Research Methods of 0.000 <0.05